2003
DOI: 10.1256/qj.01.112
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of numerical simulations to initial modifications of potential vorticity—a case‐study

Abstract: SUMMARYModi cations of numerical potential vorticity (PV) elds according to features in water vapour (WV) images are combined with singular-vector dynamics in an attempt to improve the numerical analysis in the study of a severe winter storm. The apparent mismatch between features in the WV images and upper-level PV anomalies in the numerical analysis is corrected at levels indicated as sensitive by the fastest growing singular vectors. Model reruns, based on the inverted PV elds, are then carried out. Though … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Calculation of ECMWF singular vectors, with an optimization time of 24 h and targeted at the region where the cyclone ends up after 24 h, has shown that the flow is quite sensitive to perturbations in the initial condition, in particular in the region of the mismatch. The singular vectors furthermore showed that this sensitivity is not limited to upper levels alone, in accordance with the study by Røsting et al (2003). We also considered the operational ECMWF ensemble.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Calculation of ECMWF singular vectors, with an optimization time of 24 h and targeted at the region where the cyclone ends up after 24 h, has shown that the flow is quite sensitive to perturbations in the initial condition, in particular in the region of the mismatch. The singular vectors furthermore showed that this sensitivity is not limited to upper levels alone, in accordance with the study by Røsting et al (2003). We also considered the operational ECMWF ensemble.…”
Section: Discussionsupporting
confidence: 84%
“…They can be related to regions of baroclinic instability (Hoskins et al, 2000). The idea of using singular vectors in the context of our work is inspired by the work of Røsting et al (2003) who base their potential vorticity modifications on the structure of the singular vectors on different pressure levels. Apart from modifications in the upper levels of the atmosphere (300-700 hPa), which contribute most to the improvement of the forecast, their singular vectors additionally indicate regions near the surface where the forecast is sensitive.…”
Section: Singular Vectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…After Hoskins et al (1985) elaborated the application of isentropic potential vorticity (PV) in the diagnosis of the upper-level forcing in the development of extratropical cyclones, the approach has been used in analysing PL dynamics (e.g. Montgomery and Farrel, 1992;Sunde et al, 1994;Grønås and Kvamstø, 1995;Moore and Vachon, 2002;Røsting et al, 2003;Kristjansson, 2006, Bracegirdle andGray, 2009;Wu et al, 2011). Montgomery and Farrel (1992) proposed a two-stage development process for PLs in their idealised numerical study.…”
Section: Introductionmentioning
confidence: 99%